Reflexões sobre pobreza e desigualdade no Brasil - Lavoratto, Leticia Aparecida (2017)
Poverty is a complex phenomenon of multiple dimensions, not restricted to insufficient consumption, but rather to the privations to which individuals are exposed. It was presented how multidimensional poverty is distributed through the creation of indicators of low income, vulnerabilities and poverty. After the creation of these indicators an exploratory factorial analysis was carried out to identify five levels of deprivation in which a family may be. The results showed that there is no significant difference between men and women compared to the national average in family poverty. In addition, non-white people were those with the highest rates of multidimensional poverty compared to the national average, while for the area of residence, the indicators of people residing in rural areas presented results above the national average, Evidencing the fragility of the rural environment. The states with the highest rates of multidimensional poverty for the year 2014 were Maranhão, Pernambuco and Alagoas, while the states of the South and Central West regions had the lowest rates of multidimensional poverty. Following the analyzes, it was studied how poverty in the rural environment of the state of Mato Grosso in the year 2010 is distributed. It was found that the 10 poorest municipalities presented on average a poverty index of 39%, a difference in the average of 11% among the more and less poor municipalities of the state. Although multidimensional poverty does not consider income as the main factor in determining poverty, the municipalities with the highest poverty rates also obtained the lowest incomes. In poorer municipalities there is a greater participation of men as heads of families, besides having a larger age group. The poorest municipalities presented the lowest levels of formal education, suggesting that there is a rural intervention in educational development, as a way to combat the growth of poverty rates in rural areas. Another point analyzed is about income transfer policies, where the relationship between poverty and economic development is discussed when poverty reduction programs have a level of inefficiency considered acceptable. According to the results, it is preferable to minimize the number of eligible persons who do not receive the program, even if this leads to an increase in ineligibles receiving the benefit in the wrong way. Finally, the weight of the Bolsa Família Program in the fight against poverty was evaluated, where the difference in poverty among those who need the program and do not receive and those who receive is 11.21%. For biparental and single parent families, the Bolsa Família Program represents a fall in poverty of 11.06% and 11.89% respectively, as these values are close, it is not possible to affirm that the Bolsa Família Program has greater weight for single parent families. Therefore, income transfer policies would be inefficient to meet the difference in poverty among families with a differentiated family structure, thus requiring specific policies on the subject.